A history of the animal world in the ancient Near East - Collins, Billie Jean. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2002)
This book is about all aspects of man's contact with the animal world; sacrifice, sacred animals, diet, domestication, in short, from the sublime to the mundane. Chapters on art, literature, religion and animal husbandry provide the reader with a complete picture of the complex relationships between the peoples of the Ancient Near East and (their) animals. A reference guide and key to the menagerie of the Ancient Near East, with ample original illustrations.